Influence of food additives from fish milt roe and glycerin on productivity parameters of sturgeon fish - Yurin Denis A.; Maksim Ekaterina A.; Danilova Aleksandra A.; Gneush Anna N.; Nikoghosyan Flora G. (E3S Web of Conferences, 2023)
The effect of a new feed additive “GLINMOL” in the form of emulsion on productivity of sturgeons was studied. The aim of the research was to study the effect of newly developed feed additives based on fish milt roe and glycerin on sturgeon fish productivity. The experiment consisted of two parts; groups of fish of 3-4 and 4 maturity stages were formed. The first group (control) received complete mixed feed without additives, the second - 2.0% of glycerin of total feed weight; the third - feed additive “GLINMOL” at a dose of 2.0% of total feed weight. The largest gross increase of live weight for the entire rearing period was noted when “GLINMOL” feed additive was used - 11.9% (P<0.01) higher than the control parameter. Glycerin application in the second group also exceeded the control value of live weight increase by 8.1% (P<0.05). The final body length of sturgeons in the second experimental group was almost equal to the control. In the third group, this parameter significantly exceeded the control by 0.5% (P<0.05). The values of the fatness coefficient did not differ significantly among the groups and were in the range of 1.11-1.13.